2019
DOI: 10.1111/jgs.16096
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Violence: Child Maltreatment, IPV, and Elder Abuse Phenotypes in a US Chinese Population

Abstract: OBJECTIVES: To examine the associations between violence experiences including phenotypes (psychological, physical/ sexual abuse, financial exploitation, caregiver neglect) of child maltreatment (CM), intimate partner violence (IPV), and elder abuse (EA). DESIGN: Cross-sectional data collected during 2011-2013. SETTING: US Chinese community in Chicago, Illinois. PARTICIPANTS: A total of 3157 community-dwelling older adults (aged ≥60 y). MEASUREMENTS: Cases of CM, IPV, and EA. RESULTS: Prevalence of violence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Studies suggests similar findings also among older adults, albeit rarely investigated (Hamby, Smith, Mitchell, & Turner, 2016;Ramsey-Klawsnik, 2017;Teaster, 2017;Williams, Racette, Hernandez-Tejada, & Acierno, 2017). Recently, experiences of childhood abuse have also been found to be associated with reporting abuse as well as ill-health in older age (Kong & Easton, 2018;Maschi, Baer, Morrissey, & Moreno, 2013;Wang & Dong, 2019). Hence, from a health care standpoint, a life-course perspective is well motivated.…”
Section: Introductionmentioning
confidence: 76%
“…Studies suggests similar findings also among older adults, albeit rarely investigated (Hamby, Smith, Mitchell, & Turner, 2016;Ramsey-Klawsnik, 2017;Teaster, 2017;Williams, Racette, Hernandez-Tejada, & Acierno, 2017). Recently, experiences of childhood abuse have also been found to be associated with reporting abuse as well as ill-health in older age (Kong & Easton, 2018;Maschi, Baer, Morrissey, & Moreno, 2013;Wang & Dong, 2019). Hence, from a health care standpoint, a life-course perspective is well motivated.…”
Section: Introductionmentioning
confidence: 76%
“…Fewer studies have examined multiple types of victimization that are often reported by older people [21], including emotional, physical, sexual, and financial abuse [22]. Wang and Dong [23] found significant correlations between several types of child maltreatment and elder abuse, though the researchers acknowledged that their research captured a limited range of types of abuse, and called for further research to include broader measurement across both child maltreatment and elder abuse domains.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, sí existen diferencias significativas en cuanto al tipo de maltrato, la duración del maltrato a lo largo de la vida y la frecuencia de las acciones de maltrato en el último año; en el caso de las mujeres, el inicio del maltrato se remonta más en el tiempo, y la frecuencia de los actos de maltrato en el último año es mayor. Según investigaciones recientes, no hay diferencias entre los hombres y las mujeres en la prevalencia del maltrato (Badenes-Ribera, Fabris y Longobardi, 2019; Yon y otros, 2017); sin embargo, un historial de violencia puede predisponer aún más a una persona a sufrir diferentes tipos de maltrato en la vejez (Wang y Dong, 2019). En nuestro estudio, consideramos que en el caso de algunas mujeres se está registrando un aumento de la violencia de género.…”
Section: G Discusiónunclassified